(untitled) (Journal of Informatics Education and Research, 2025)
Short‑form video platforms (e.g., TikTok, Instagram Reels, YouTube Shorts) have evolved into potent sources of financial information and behavioral cues for retail investors. The unique blend of brevity, virality, and algorithmic curation fosters new pathways of influence where financial decisions are increasingly shaped by short, engaging clips rather than traditional information channels. Drawing from behavioral finance theories, particularly attention‑induced trading and social proof, this paper examines how exposure to finance‑oriented short‑form content influences portfolio decisions, risk preferences, and trading horizons. A comprehensive conceptual model is developed linking platform design features (algorithmic feeds, engagement metrics, and creator incentives) to investor outcomes through mediators (attention capture, perceived social norms, reduced deliberation) and moderators (financial literacy, platform intensity, creator credibility). By integrating insights from cross‑disciplinary research—finance, psychology, media studies, and human‑computer interaction—we identify both risks (herding, impulsive risk‑taking, shorter holding periods) and opportunities (increased literacy, democratized access). We further provide regulatory and design implications for enhancing content quality, integrating friction into trading apps, and supporting financial education. This paper contributes by bridging the gap between digital media studies and behavioral finance, presenting a research agenda for scholars and policymakers in the digital investing age.